Antibacterial activity of crude ethanolic extracts of pummelo [Citrus maxima (Burm.) Merr.] on Listeria monocytogenes and Staphylococcus aureus. - Barrion, A. S. A.; Mabesa, R. C.; Dizon, E. I.; Hurtada, W. A. (2003)
The antibacterial activity of the ethanol extracts of the pericarp, mesocarp and segment membrane of the pummelo fruit against Listeria monocytogenes and Staphylococcus aureus was assessed by measuring inhibition zones using the cup cylinder techniques. Inhibition zones were significantly different (p<0.05) based on the fruit material extracted and extract concentration. Among the fruit extracts; the pericarp extract displayed the highest antimicrobial effect with mean zone of inhibition of 9.90 and 15.25 mm for S. aureus and L. monocytogenes was inhibited more by the mesocarp extract (13.95 mm) than the segment membrane extract (12.75 mm). This study provides evidence that pummelo can be a potential source of natural antimicrobial and suggests the possibility of utilizing it to organically preserve food items.
Keywords: Pummelo; Antibacterial agents; Ethanol; Food preservatives